Human development and Covid-19 lethality rate: Ecological study in America - Carhuapoma-Yance, Mario (2021)
Background: The Human Development Index (HDI), uses three dimensions of development such as life expectancy, access to education and income level. It has been seen worldwide that socioeconomically vulnerable groups are the least protected and face the highest risk of COVID-19. This study aims to evaluate the correlation between HDI, GINI inequality index and COVID-19 case fatality rate in American countries. Study: An ecological observational study was developed, using COVID-19 metrics from Latin American countries. The outcome variable was COVID-19 case fatality rate, and the exposure variables were HDI, GINI, life expectancy, years of schooling, proportion of people over 60 years of age and GDP per capita. Once the data were collected, analyses were performed. We used the spearman correlation method, with a significance level of 95%. Findings: Twenty-four Latin American countries were evaluated, finding a COVID 19 case fatality rate with a median of 2.41 and with 1.55 and 3.04 as 25th and 75th percentile respectively, obtaining also with extreme values Ecuador, Mexico and Peru with 6.41, 7.57 and 9.12 respectively. When evaluating the correlation of the COVID 19 case fatality rate, a weak negative linear correlation was found between HDI, schooling index and life expectancy with rho= -0.253, -0.342 and -0.342 respectively, however, statistical significance was not found (p-value >0.05). Conclusions: It was found among Latin American countries that there is a weak negative linear correlation between COVID 19 case fatality rate and HDI, schooling index and life expectancy.